Premature mortality due to alcohol-related diseases of the liver in Poland according to voivodships - Paciej, Paulina; Ciabiada, Beata; Maniecka-Bryła, Irena (Family Medicine & Primary Care Review, 2017)
Background . Alcohol is one of the most serious public health threats facing the global population. Of all disease risk factors, alcohol ranks ninth place globally and sixth in Poland, with regards to DALYs (Disability-Adjusted Life Years). DALYs consist of two components: YLL (Years of Life Lost) and YLD (Years of Life with Disability). Objectives . The aim of the study was to assess the number of years of life lost due to alcohol-related diseases of the liver in the Polish population in 2013 according to voivodships. Material and methods . The study was based on 387,312 records obtained from the death certificates of Poles who died in 2013. The data on deaths caused by alcohol-related diseases of the liver (alcoholic liver disease, fibrosis and cirrhosis of the liver) were used for the analysis. The SEY LL (Standard Expected Years of Life Lost) was used to calculate the years of life lost. Results . In 2013, alcohol-related diseases of the liver caused 6,126 deaths of Poles, resulting in a loss of 129,578.8 years of life in the group of men (69.5 per 10,000) and 51,280.3 years in the group of women (25.8 per 10,000). The highest number of years of life lost was noted in the voivodships of Śląskie (102.5 per 10,000 males and 45.9 per 10,000 females) and Łódzkie (97.3 and 33.6, respectively), and the lowest in Podkarpackie (49.3 and 10.4, respectively). Conclusions . Premature deaths caused by alcohol-related diseases of the liver are a considerable problem in the Polish population. The particular challenge in public health activities is to reduce the inconsistencies in health between voivodships.